The Association Study of IL-23R Polymorphisms With Cerebral Palsy in Chinese Population - Wang, Yangong; Xu, Yiran; Fan, Yangyi; Bi, Dan; Song, Juan; Xia, Lei; Shang, Qing; Gao, Chao; Zhang, Xiaoli; Zhu, Dengna; Qiao, Yimeng; Su, Yu; et al. (Frontiers in Neuroscience, 2020)
Background: Cerebral palsy (CP) is a syndrome of non-progressive motor dysfunction caused by early brain development injury. Recent evidence has shown that immunological abnormalities play an important role in the development of CP. Methods: We recruited 782 children with CP as the case group and 770 healthy children as the control group. The association between IL-23R (rs10889657, rs6682925, rs1884444, rs17375018, rs1004819, rs11805303 and rs10889677) and CP was studied with the case-control method. Subgroup analysis based on complications and clinical subtypes was further carried out. The genotype distributions of all six SNPs among all control subjects showed no significant deviation from Hardy-Weinberg equilibrium. Results: Differences in the allele and genotype frequencies of the rs11805303 and rs10889677 SNPs were detected (Pallele = 0.014 and 0.048, Pgenotype = 0.023 and 0.008), and the difference in genotype frequency of rs10889677 remained statistically significant after Bonferroni correction (Pgenotype = 0.048). Subgroup analysis revealed a more significant association of rs10889677 with CP accompanied by global developmental delay (Pgenotype = 0.024 after correction) and neonatal encephalopathy (Pgenotype = 0.024 after correction). Conclusion: The results in this study showed a significant association of IL-23R with CP, suggesting that the IL-23R may play a potential role in the pathogenesis of CP.